Effect of atmospheric conditions on the onset electric field of ZnO and Y2O3 ceramics flash sintering at room temperature. Issue 24 (15th December 2021) - Zhou, Hongyang; Li, Xiang; Huang, Rongxia; Yan, Nianping; Wang, Xilin; Jia, Zhidong
Abstract: Flash sintering of zinc oxide (ZnO) ceramics can be induced at room temperature (25 °C) by electrical breakdown at high electric field strength. However, a strong discharge may degrade the sample. This study investigated the effects of atmospheric pressure and composition on the onset electric field for the flash sintering of ZnO. The experimental results show that flash sintering of ZnO under a low electric field at room temperature can be achieved by adjusting the atmospheric conditions. Compared with the onset electric field strength under normal atmospheric conditions, the value for flash sintering of ZnO at 20 kPa in a mixture of 20% air +80% argon (Ar) can be reduced by 82% to approximately 700 V/cm. This method also applies to yttrium oxide (Y2 O3 ) for a low electric field in flash sintering at room temperature, and is the first report on flash sintering of Y2 O3 at room temperature.